PLACE ATTACHMENT IN TRADITIONAL URBAN NEIGHBOURHOODS - Umar Faruq Muhammad, Wan Mohd Zakri bin Wan Abdullah, Zulai Jarmai Baba-Girei, Ahmed Osman Ibrahim, Ango Joseph Aaron, Kasiemobi Collins Okoye (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Place attachment is a phenomenon, extensively studied by researchers from different fields, within different contexts and from different perspectives. Within the context of the traditional urban built environment, and using an explanatory narrative mechanism, this study traced the phenomenon by reilluminating its impact evidenced in the perpetual existence of traditional neighbourhoods in urban areas, despite apparent developmental neglect in some of those neighbourhoods. Consequently, place attachment to the traditional urban built environment was shown to be higher than in new urban developments, as a result of satisfaction with the liveliness, neighbourliness and diversity of such environments.